The Influence of Online Learning and Parental Involvement Towards Early Childhood Social Emotional Intelligence - Nurhafizah; Indriyani, Tuti; Zukhairina (Yayasan pendidikan dzurriyatul Quran, 2024)
This study aims to determine the effect of online learning on emotional social intelligence, parental involvement on emotional social intelligence and the influence of online learning and parental involvement on emotional social intelligence. This research is a quantitative study using a path analysis approach. parental involvement on children's emotional social intelligence is 14.8% with a total count of 1,613 <2,000, meaning that H0 is accepted, H1 is rejected and the influence between online learning and parental involvement on children's emotional social intelligence is 33.4% with a total score of 14,269>2,000 , meaning that H0 is rejected and H1 is accepted. Based on the results of this study, it is informed that online learning and parental involvement if carried out partially do not have a significant effect, but if carried out together, it will affect the process of increasing children's emotional social intelligence.